Errata Corrige: Med Lav 2016; 107 (4): 315-326 - P.G. Barbieri, A.B. Somigliana - Asbestos-related diseases and biological index of cumulative dose in shipyard workers (1996-2015) - Redazione, La (La Medicina del Lavoro, 2016)
The authors reported an error that need to fully replace the data already published. The mistake is in Table 3 and the incorrect information may interfere with the results’ interpretation, misleading the reader.